Exploring Helping Professionals Attitudes toward Clients with Antisocial Personality Disorder - Dunbar Jr, Edward T; Leierer, Stephen; Hurt-Avila, Kara; Elliott, Anna (International Journal of Psychosocial Rehabilitation, 2021)
There is a lack of research regarding helping professionals’ attitudes toward clients withantisocial personality disorder (ASPD). We examined factors associated with helpingprofessionals’ attitudes toward clients with ASPD through an online survey using a modifiedversion of a validated instrument. We found the following three factors: security, acceptance,and enjoyment influenced helping professionals’ attitudes towards clients with ASPD.Implications for clinical training, supervision, and education toward this population arediscussed